How many bone metastases may be defined as high‐volume metastatic prostate cancer in Asians: A retrospective multicenter cohort study. Issue 5 (3rd February 2020) - Yamada, Yasutaka; Sakamoto, Shinichi; Rii, Junryo; Yamamoto, Satoshi; Kamada, Shuhei; Imamura, Yusuke; Nakamura, Kazuyoshi; Komiya, Akira; Nakatsu, Hiroomi; Ichikawa, Tomohiko
Abstract: Background: Recent landmark randomized trials (CHAARTED and LATITUDE studies) have highlighted potent upfront therapy for "high‐volume" and "high‐risk" metastatic castration‐naïve prostate cancer (mCNPC). However, treatment response shows racial differences. We aimed to propose a novel definition for "high‐volume" prostate cancer in Asians. Methods: We retrospectively pursued 426 patients with de novo mCNPC from multiple institutions between 1999 and 2017. All patients received androgen deprivation therapy alone as initial treatment. We evaluated the number of bone metastases at diagnosis to clarify the clinical significance for progression‐free survival and overall survival (OS). Statistical analyses were conducted using the Mann‐Whitney U test, Cox proportional hazard models, and Kaplan‐Meier methods. Results: Median age and prostate‐specific antigen level were 73 years and 266.2 ng/ml, respectively. Median OS was 55.5 months in patients who met the CHAARTED high criteria (vs 33.1 months in the trial). We evaluated 5 thresholds in the number of bone metastases (≥4, ≥6, ≥11, ≥16, and ≥21) to investigate the prognostic values. Patients with ≥11 bone metastases showed the highest HR for OS (2.766). Patients with 11 to 20 bone metastases had a significantly shorter OS than those with ≤10 metastases ( P = .0001). We, therefore, proposed modified CHAARTED and LATITUDE high criteria (extending bone metastases ≥11). In multivariate analysis, the modified criteria were the only independent prognostic factors for OS ( P = .0272 and P = .042, respectively). Conversely, no significant differences in OS were seen between patients with 1 to 3 bone metastases and 4 to 10 ( P = .7513). Conclusion: Our exploratory study suggested ≥11 bone metastases as a suitable definition for "high‐volume" prostate cancer in Asians. A larger, prospective study is warranted to verify our findings.